Evaluation of miR‐130 family members as circulating biomarkers for the diagnosis of bladder cancer. Issue 12 (5th August 2020) - Wang, Jingyao; Zhao, Liwen; Peng, Xiqi; Liu, Kaihao; Zhang, Chunduo; Chen, Xuan; Han, Yanni; Lai, Yongqing
Abstract: Objective: Previous research has shown that the miR‐130 family is closely related to the occurrence and development of bladder cancer. We hope to use the miR‐130 family members as new, non‐invasive, and easily detectable biomarkers for bladder cancer. Methods: We analyzed 428 cases in The Cancer Genome Atlas‐Bladder Urothelial Carcinoma database and verified that the miR‐130 family members were significantly overexpressed in bladder cancer. A total of 74 bladder cancer patients and 90 controls were enrolled. The relative expression of the miR‐130 family in serum was detected using quantitative reverse transcription‐polymerase chain reaction. The diagnostic efficacy of the miR‐130 family members was determined using the receiver operating characteristic method (ROC), and a diagnostic panel was built using logistic regression. The results of the study were further confirmed in an external validation set of 492 samples from the Gene Expression Omnibus database. Results: The expression of the miR‐130 family members (except for miR‐301b‐3p) in the serum of bladder cancer patients was higher than that in the controls. The diagnostic capabilities for bladder cancer were 0.847 (miR‐130a‐3p), 0.762 (miR‐130b‐3p), and 0.892 (miR‐301a‐3p). We established a three‐miRNA panel with an area under the ROC curve as high as 0.961, indicating that it is a promising clinical diagnostic biomarker of bladder cancer with high sensitivity and specificity. Conclusion: The expression levels of miR‐130 family members in serum can effectively distinguish the bladder cancer patients from healthy controls. This finding will facilitate the clinical diagnosis of bladder cancer. Abstract : The miR‐130 family members are highly expressed in the serum of bladder cancer patients. Their expression levels can effectively distinguish bladder cancer patients from healthy controls.